2023
DOI: 10.1021/acs.jctc.3c00507
|View full text |Cite
|
Sign up to set email alerts
|

How Good Are Current Docking Programs at Nucleic Acid–Ligand Docking? A Comprehensive Evaluation

Abstract: Nucleic acid (NA)–ligand interactions are of paramount importance in a variety of biological processes, including cellular reproduction and protein biosynthesis, and therefore, NAs have been broadly recognized as potential drug targets. Understanding NA–ligand interactions at the atomic scale is essential for investigating the molecular mechanism and further assisting in NA-targeted drug discovery. Molecular docking is one of the predominant computational approaches for predicting the interactions between NAs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The active components of Chinese medicinal materials were obtained from the TCMSP database [ 22 ]. LeDock was used for molecular docking, and the results were split into several PDB files [ 23 ]. The protein structure was imported into Maestro 13.5 for visualization [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…The active components of Chinese medicinal materials were obtained from the TCMSP database [ 22 ]. LeDock was used for molecular docking, and the results were split into several PDB files [ 23 ]. The protein structure was imported into Maestro 13.5 for visualization [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…A recent study conducted by Agarwal et al showed that rDOCK, a RNA–ligand docking method, outperformed AutoDock Vina in pose prediction . However, in another study conducted by Jiang et al, protein–ligand docking tools showed more promising performance than RNA–ligand docking methods . Although these docking methods were evaluated for pose prediction and binding affinity prediction, their ability to rank active and inactive ligands against RNA targets was not assessed, which is important for performing virtual screening campaigns.…”
Section: Introductionmentioning
confidence: 99%